PERSEPSI MAHASISWA UNIVERSITAS TERBUKA BOGOR TERHADAP TREN TUWEB SEBAGAI LAYANAN BELAJAR DARING - Sukma Wahyu Wijayanti; Stefani Nawati Ekoresti; Enang Rusyana (Universitas Terbuka, 2022)
This study aims to analyze the perception of UPBJJ-UT Bogor students towards the implementation of webinar tutorial learning (tuweb) as a substitute for face-to-face tutorial services (TTM) during the Covid-19 pandemic. The sample in this study was selected by random sampling technique and involved 400 student respondents. Research data were collected using an electronic questionnaire and analyzed using descriptive statistical analysis to describe students' perceptions of readiness and implementation during tuweb learning. The results showed that students had a good perception of the implementation of tuweb, including accessibility, device ownership, ability to use technology, ease of obtaining materials, ease of learning materials, interactivity, learning independence, and satisfaction with tutor abilities.